Rarely $s$-$(τ_1,τ_2)p$-continuous Multifunctions (European Journal of Pure and Applied Mathematics, 2025)
This paper is concerned with the concepts of upper rarely $s$-$(τ_1,τ_2)p$-continuous multifunctions and lower rarely $s$-$(τ_1,τ_2)p$-continuous multifunctions. Furthermore, some characterizations and several properties concerning upper rarely $s$-$(τ_1,τ_2)p$-continuous multifunctions and lower rarely $s$-$(τ_1,τ_2)p$-continuous multifunctions are established.
Keywords: $(τ_1,τ_2)p$-open set; upper rarely $s$-$(τ_1,τ_2)p$-continuous multifunction; lower rarely $s$-$(τ_1,τ_2)p$-continuous multifunction